PENGARUH MODEL PEMBELAJARAN COURSE REVIEW HORAY UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS V SEKOLAH DASAR - Setyaningsih, Yulia Ratna Hesti; Mushafanah, Qoriati; Saputra, Henry Januar (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2019)
This study aims to: 1) improve the activity and learning outcomes of class V students on theme 7 sub-themes 1, 2) to find out the influence of the learning model of the horay course review to improve the activity and learning outcomes of class V students in theme 7 of sub-theme 1. Quantitative research uses the Pre Experimental Design design with the form of One Group Pretest-Posstest Design. The population in this study were all VA classes at SD Negeri 03 Kayen consisting of 20 students. The results in this study were obtained from the pretest and posstest values and observations for learning activities. T-test results obtained by tcount = 8.339 with t table = 2.086 then tcount>ttable which means that the Course Review Horay learning model can improve student learning outcomes. In addition, student learning activities can also achieve good criteria as evidenced by the analysis of observation sheets that have been carried out. As well as the differences in student learning outcomes of the pretest and posttest by applying the Course Review Horay learning model as evidenced by the average gain obtained 45% were categorized as "Moderate". The results of classical completeness initially only 40% to 90%.